FA Sliding as the Mechanism for the ANT1-Mediated Fatty Acid Anion Transport in Lipid Bilayers - Kreiter, Jürgen; Škulj, Sanja; Brkljača, Zlatko; Bardakji, Sarah; Vazdar, Mario; Pohl, Elena E (International journal of molecular sciences, 2023)
Mitochondrial adenine nucleotide translocase (ANT) exchanges ADP for ATP to maintain energy production in the cell. Its protonophoric function in the presence of long-chain fatty acids (FA) is also recognized. Our previous results imply that proton/FA transport can be best described with the FA cycling model, in which protonated FA transports the proton to the mitochondrial matrix. The mechanism by which ANT1 transports FA anions back to the intermembrane space remains unclear. Using a combined approach involving measurements of the current through the planar lipid bilayers reconstituted with ANT1, site-directed mutagenesis and molecular dynamics simulations, we show that the FA anion is first attracted by positively charged arginines or lysines on the matrix side of ANT1 before moving along the positively charged protein-lipid interface and binding to R79, where it is protonated. We show that R79 is also critical for the competitive binding of ANT1 substrates (ADP and ATP) and inhibitors (carboxyatractyloside and bongkrekic acid). The binding sites are well conserved in mitochondrial SLC25 members, suggesting a general mechanism for transporting FA anions across the inner mitochondrial membrane.
Keywords: Lipid Bilayers; adenosintrifosfát; lipidové dvojvrstvy; Adenosine Triphosphate; mastné kyseliny; protony; mitochondriální ADP/ATP-translokasy; Protons; Mitochondrial ADP, ATP Translocases; Fatty Acids; anionty; Anions